Financial Accountants' Perceptions of Management's Ethical Standards - D'Aquila, Jill M. (Journal of business ethics, 2001)
It is believed that the atmosphere in which employees carry out their responsibilities influences whether employees will behave ethically. An important factor contributing to the integrity of the financial reporting process is the tone set by senior management (i.e., the corporate environment). This study was conducted to describe financial accountants' perceptions of management's ethical standards. These perceptions are based on both management's actions and management's expectations of the employee. This researcher also attempted to identify demographic variables that are related to these perceptions. The results are based on a survey mailed to 400 CPAs who prepare financial reports. Accountants generally perceive management's conduct as ethical and believe that management expects them to behave ethically. Of particular interest is that respondents have more positive attitudes about management's expectations of them than they do about management's own actions in terms of ethical behavior. The majority of respondents reported at least some pressure to achieve short-term performance targets. Management level, industry, size of an organization, and gender were all found to be related to employee perceptions.